Marc Brown's Arthur's birthday. - Brown, Marc Tolon (Living Books, 1994)
Multimedia presentation of the story about the dilemma that arises when Muffy schedules her birthday party for the same day as Arthur's birthday party. Each scene provides text (in English or Spanish), animations, sound effects, and music (including audio tracks which play on compact disc audio players). Features demonstration versions of seven similar products by the publisher.